2009
DOI: 10.1158/1535-7163.mct-09-0179
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian carcinoma cells with low levels of β-F1-ATPase are sensitive to combined platinum and 2-deoxy-d-glucose treatment

Abstract: We have here examined chemopotentiating effects of glycolysis inhibitor 2-deoxy-D-glucose (DG) in two epithelial ovarian carcinoma (EOC) cell lines and 17 freshly isolated ascitic EOC cell samples, and we identify low expression of the β-F1-ATPase involved in mitochondrial ATP production as a candidate marker for sensitivity to this strategy. Although in the majority of samples, DG per se did not induce apoptosis, cotreatment with DG potentiated apoptosis and total antiproliferative effects of cisplatin and, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 26 publications
3
32
0
1
Order By: Relevance
“…We have here and earlier observed that SKOV-3/SKOV-3-R cells are highly dependent on glutamine but not on glucose, and are not sensitive to 2-DG; furthermore, that unlike 3-BP, 2-DG does not greatly potentiate cisplatin 27 (and not shown). Here, both SKOV-3 and SKOV-3-R proliferated well in galactose medium in the absence of glucose, but when cisplatin was added to the galactose medium, SKOV-3-R were more sensitive than SKOV-3 cells.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…We have here and earlier observed that SKOV-3/SKOV-3-R cells are highly dependent on glutamine but not on glucose, and are not sensitive to 2-DG; furthermore, that unlike 3-BP, 2-DG does not greatly potentiate cisplatin 27 (and not shown). Here, both SKOV-3 and SKOV-3-R proliferated well in galactose medium in the absence of glucose, but when cisplatin was added to the galactose medium, SKOV-3-R were more sensitive than SKOV-3 cells.…”
supporting
confidence: 67%
“…The halfmaximal inhibitory concentrations (IC 50 ) over 72 h and regrowth capacity (48 h drug treatment followed by another 72 h in drugfree medium) were assessed based on total cellular protein in the samples, in turn assessed using the Sulforhodamine B assay (Sigma-Aldrich) according to manufacturer's instructions. For details, see Hernlund 27 and Björklund.…”
mentioning
confidence: 99%
“…During ischemia, the ATP hydrolytic activity of the enzyme is inhibited by the ATPase inhibitory factor 1 (IF1 In oxidative phosphorylation, ATP is synthesized by the mitochondrial ATP synthase, a H ϩ -driven rotatory engine of the inner membrane that utilizes as driving force for ATP synthesis the H ϩ electrochemical gradient generated by the respiratory chain (1-4). The cellular expression level of ␤-F1-ATPase, 2 which is the catalytic subunit of the H ϩ -ATP synthase, is diminished in diverse human pathologies (5), which include cancer (6 -9), affording a relevant marker of disease progression (6, 7, 10 -12) and of the response to chemotherapy (7,(13)(14)(15). Moreover, the down-regulation of ␤-F1-ATPase in lung carcinomas (12) and colon cancer cells (15) also provides a mechanistic explanation to the increased glucose avidity of carcinomas, i.e.…”
Section: The Hmentioning
confidence: 99%
“…The cellular expression level of ␤-F1-ATPase, 2 which is the catalytic subunit of the H ϩ -ATP synthase, is diminished in diverse human pathologies (5), which include cancer (6 -9), affording a relevant marker of disease progression (6, 7, 10 -12) and of the response to chemotherapy (7,(13)(14)(15). Moreover, the down-regulation of ␤-F1-ATPase in lung carcinomas (12) and colon cancer cells (15) also provides a mechanistic explanation to the increased glucose avidity of carcinomas, i.e.…”
mentioning
confidence: 99%
“…In our previous work [16], we applied a lasso penalized Cox regression method, for the first time, to investigate the signature genes that are correlated to the pancreatic cancer survival time. We identified 12 genes associated with the pancreatic cancer survival and eight of them have been confirmed to be genetically altered and differentially expressed in the cancer of gastric, colorectal, ovarian, breast, skin, kidney, colon, lung, and pancreatic in in vivo and in vitro experiments [17-25]. It has been shown that these survival-associated genes can also help to grade the stage and estimate the survival time of the PDAC patients.…”
Section: Introductionmentioning
confidence: 99%